The Implementation of Character Education at Ar-Rahmah Integrated Islamic Elementary School of Makassar - Syahruddin Syahruddin (Al-Ulum, 2015)
The implementation of character education as reflected in QS Luqman: 12-19 at the Ar-Rahmah Integrated Islamic Elementary School of Makassar learners is integrated into the whole school programs. Those programs namely: integrated in every subjects, the development of school culture, extra-curricular activities, cooperation with learners’ parents, the control card (yaumian card) and means of communication via group in website. The impact of character education on learners’ attitude and behavior can be identified from their daily attitude and behavior like being discipline, praying dhuha, praying dhuhur in congregation, keeping the school environment clean, keeping mutual appreciating among their friends, being responsible towards the task assigned by the teachers, maintaining order in the learning process, and asking for permission when they want to get out.